Continuity and change in the South African minibus taxi industry - Seftel, Lisa (My University, 2022)
This dissertation seeks to identify the key features of the South African minibus taxi industry and understand the forces that have shaped it. The author, through qualitative interviews and participant observation, describes and analyses the different layers in the minibus taxi industry, from drivers to the national structures and how the taxi industry interacts with the state and private sector. A pervasive feature of the industry is the centrality of the role of violence, which is also explored as a strategic resource and binding constraint to change in the taxi industry. The dissertation aimed to establish the extent to which there has been continuity and change over the forty years of existence of the minibus taxi industry but concludes that there is an unyielding continuity in how the industry is structured and functions, to the benefit of a relatively few taxi leaders. In contrast, taxi drivers and owners of taxi vehicles continue to be marginalised from achieving decent livelihoods and accumulating wealth. In this context, the prospects of change where the needs of commuters are met, the state can fulfil its public transport mandate, and the taxi industry as a whole can prosper are poor. A prerequisite to change is an improved understanding by policy makers of who holds power in the taxi industry and the ability of the state to introduce measures to shift the balance of power to the majority of owners of taxi vehicles
Dissertation presented in fulfilment for the degree of Master of Management to the School of Governance, Faculty of Commerce, Law and Management, University of the Witwatersrand, 2021
Keywords: UCTD; Minibus taxi industry; Taxi operators; Drivers; Taxi violence; SDG-8: Decent work and economic growth